SERVICE QUALITY AND CUSTOMER SATISFACTION INCREASING LOYALTY OF PASSENGERS RO-RO FERRY BAKAUHENI - Reza Fauzi Jaya Sakti; Prima Widiyanto; Primadi Candra Susanto (ABNUS Publisher, 2021)
This study uses a quantitative method with descriptive analysis, distributing questionnaires to passengers or users of the roro ship in Bakaheuni, Merak. This research was conducted with the objectives of the research being: To find out how the online ticket sales system is based, To find out the handling of delays on ro-ro ferries, To find out how to set up parking management at the wharf, To find out how to optimize the dock operation, To find out the process of managing the operating fleet. Result of this research the magnitude of the positive relationship of service quality and customer satisfaction with service passenger loyalty of 75.8%, while the rest is the relationship of other factors that are not analyzed in this model.